2021
DOI: 10.3389/fimmu.2021.767868
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-Like Protein 1 Serves as an Anti-Inflammatory Agent for Collagen-Induced Arthritis Therapy in Mice

Abstract: Fibrinogen-like protein 1 (FGL1) was recently identified as a major ligand of lymphocyte-activation gene-3 (LAG-3) on activated T cells and serves as an immune suppressive molecule for regulation of immune homeostasis. However, whether FGL1 has therapeutic potential for use in the T cell-induced the autoimmune disease, rheumatoid arthritis (RA), is still unknown. Here, we attempted to evaluate the effect of FGL1 protein on arthritis progression. We also evaluated potential adverse events in a collagen-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Normally, FGL1 is secreted by hepatocyte cells of the liver. 19,20 However, it is possible that WT cells also produce FGL1. 16 According to Qian et al, 16 the gene that produces FGL1 is located on human chromosome 8p22 and is present in all human somatic cells, although normally only hepatocyte cells express it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, FGL1 is secreted by hepatocyte cells of the liver. 19,20 However, it is possible that WT cells also produce FGL1. 16 According to Qian et al, 16 the gene that produces FGL1 is located on human chromosome 8p22 and is present in all human somatic cells, although normally only hepatocyte cells express it.…”
Section: Discussionmentioning
confidence: 99%
“…19 Under normal conditions, FGL1 is physiologically secreted by hepatocyte cells. 19,20 However, FGL1 was also highly expressed in various tumors such as lung, prostate, melanoma, colorectal, breast, and brain tumors. 16,19 This high expression of FGL1 in tumor cells contributes to the growth and development of neoplasms causes host lymphocyte cells (Tumor Infiltrating lymphocytes) to become cell exhausted, a condition in which lymphocytes lose their ability to kill tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Above evidences show a controversial role of FGL1 in inflammatory diseases. Deficiency of FGL1 can induce spontaneous dermatitis in gene knockout mice, and supplement of FGL1 recombinant protein improves collagen-induced arthritis ( Wang et al, 2019 ; Lin et al, 2021 ). These evidences verify the function of FGL1 regulating autoimmunity and immune homeostasis via binding to lymphocyte-activation gene 3 (LAG-3) to inhibit T cell activation ( Wang et al, 2019 ; Lin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of FGL1 can induce spontaneous dermatitis in gene knockout mice, and supplement of FGL1 recombinant protein improves collagen-induced arthritis ( Wang et al, 2019 ; Lin et al, 2021 ). These evidences verify the function of FGL1 regulating autoimmunity and immune homeostasis via binding to lymphocyte-activation gene 3 (LAG-3) to inhibit T cell activation ( Wang et al, 2019 ; Lin et al, 2021 ). However, on the other hand, inhibition of LAG-3 initiates intestinal inflammation by disturbing the immunosuppressive function of Treg cells ( Bauché et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen-like protein 1 (FGL1) is a member of the fibrinogen family and can be recognized as an immune checkpoint target through an immune escape mechanism ( 27 ). FGL1 functions as an anti-inflammatory agent in collagen-induced RA ( 28 ). Subsequent investigations have demonstrated that FGL1 contained in MSCs-Exo exhibits therapeutic effects on RA without significant adverse reactions.…”
Section: Exosomes Derived From Mesenchymal Stem Cellsmentioning
confidence: 99%